التفاؤل لدى عينة من طلاب المرحلة التفاؤل لدى عينة من طلاب المرحلة الثانوية وعلاقته بالسلوك التوكيدي في مدينة حلب: دراسة في مدينة حلب (Journal of Hama University, 2022)
Optimism among a sample of high school students and its relationship to assertive behavior in the city of AleppoFayez Khleif AlhusseinDepartment of Psychological Counseling - College of Education -University of AleppoFayez1974@gmail.com963934555160+AbstractThe aim of the research is to study optimism and its relationship to assertive behavior among high school students in the city of Aleppo and to study the differences in these two variables according to the variable of gender and the variable of specialization (scientific - literary - professional). The Arabization of Badari and El-Shennawi in 1986, the validity and reliability of the tools used were verified and all of them were validated with good validity and consistency. Gender differences in assertive behavior in favor of males as well, meaning that males have higher assertive behavior than females, and the research also found that there are differences between disciplines in optimism in favor of students of professional specialization, as they showed higher optimism than among students of literary specialization, and it was also found that optimism is capable. Predicting assertive behavior, and in this aspect it is necessary to focus on the importance of the positive aspects and their role in the assertive behavior of high school students, that is, knowing the student’s score on the optimism scale predicts a degree The student’s awareness of the affirmative behavior and the expectation of his behavior corresponding to this degree of optimism.Hence the importance of optimism and its great association with assertive behavior, and therefore attention must be paid to supportive developmental programs in schools to play a greater role in improving and developing the relationship between positive concepts and assertive behavior in the individual from the early beginnings of its preparation in the first years of school.Key words: optimism, assertive behavior, high school students in Aleppo.